Study on Environmental and Lifestyle Factors for the North–South Differential of Cardiovascular Disease in China - Wang, Mengqi; Huang, Yi; Song, Yanxin; Chen, Jianwei; Liu, Xiaoxiao (Frontiers in Public Health, 2021)
Human death and life span are closely related to the geographical environment and regional lifestyle. These factors considerably vary among counties and regions, leading to geographical disparity of disease. Quantitative studies on this phenomenon are insufficient. Cerebrovascular and heart diseases are the leading causes of death. The mortality rate of cerebrovascular and heart diseases is statistically higher in northern than in southern China; p value of t-test for cerebrovascular and heart diseases was 0.047 and 0.000, respectively. The population attribution fraction of 12 major risk factors for cardiovascular disease in each province was calculated based on their exposure and relative risk. The results found that residents in northern China consume high sodium-containing food, fewer vegetables, and less sea food products and tend to be overweight. Fine particulate matter is higher in northern than in southern China. Cold temperatures also cause a greater number of deaths than hot temperatures. All these factors have resulted in a higher cardiovascular disease mortality rate in northern China. The attributive differential for sodium, vegetable, fruit, smoking, PM2.5, omega-3, obesity, low temperature, and high temperature of heart disease between the two parts of China is 9.1%, 0.7%, −2.5%, 0.1%, 1.4%, 1.3%, 2.0%, 4.7%, and −2.1%, respectively. Furthermore, the attributive differential for the above factors of cerebrovascular disease between the two parts of China is 8.7%, 0.0%, −5.2%, 0.1%, 1.0%, 0.0%, 2.4%, 4.7%, and −2.1%. Diet high in sodium is the leading cause of the north–south differential in cardiovascular disease, resulting in 0.71 less years of life expectancy in northern compared with that in southern China.